Bevrijding met geest notities voor een nieuwe spiritualiteit. - Sobrino, Jon S.J. 1938-; Deelen, F. (Averbode Altiora, 1988)
Essay on liberation theology and liberation spirituality, especially regarding the Roman Catholic Church in El Salvador and Latin America. Explicit reference is made to the slain archbishop Oscar Arnulfo Romero of San Salvador.
Keywords: 241.1*31 -- Politieke theologie. Bevrijdingstheologie. Ethiek van de revolutie